Konsep Amanah dalam Pandangan Islam dan Kristen - Nurhidayah, Nurhidayah; Andy, Safria; Faishal, Muhammad (ANWARUL, 2024)
This research aims to analyze and compare the concept of trust in Islamic and Christian views. Through a qualitative approach, data was collected from primary sources such as the Al-Qur'an, Hadith, and Christian holy books, and also from theological and philosophical literature relevant to the concept of trust in both religions. The analytical method is carried out by exploring verses from the Koran and the Christian Bible related to trust, as well as studying classical texts and comments by Christian scholars and theologians related to this concept. In addition, interviews with religious scholars from both traditions were also conducted to gain a deeper understanding. Research findings show that despite differences in terminology and emphasis, the concept of trust in Islam and Christianity has many similarities, especially in terms of integrity, honesty and responsibility. Both the Qur'an and the Bible emphasize the importance of maintaining trust, both in spiritual and worldly affairs, as part of moral and ethical obligations. This study also highlights how both religions view trust as an important moral foundation in building human relationships with God and with fellow humans. In the context of modern society, a deep understanding of the concept of trust from Islamic and Christian perspectives can make a valuable contribution in shaping individual character and morality and strengthening the values of justice, integrity and social responsibility.